2021
DOI: 10.1155/2021/9976488
|View full text |Cite
|
Sign up to set email alerts
|

Research on Vibration Reduction Method of Nonpneumatic Tire Spoke Based on the Mechanical Properties of Domestic cat’s Paw Pads

Abstract: Although there is no risk of puncture, the vibration problem caused by discontinuous structures limits nonpneumatic tire development (NPT). The vibration reduction of nonpneumatic tires is a solvable urgent problem. This current study analyzed the dynamic grounding characteristics and the vibration reduction mechanism of the cat’s paw pads and then applied the mechanical properties to the bionic design of nonpneumatic tire spokes to solve the vibration problem. Domestic cats’ paw pads’ dynamic grounding charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Ti 2 AlN porous ceramics with a three-dimensional framework structure and relatively uniform pores were prepared. Zhou et al [ 13 ] used ZrO 2 as the raw material, MgO and CeO 2 as stabilizers, and prepared ZrO 2 porous ceramics with an excellent performance by sintering organic foam impregnation method. The effects of stabilizer types on shrinkage, surface morphology, and high-temperature phase content of ceramic samples were studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ti 2 AlN porous ceramics with a three-dimensional framework structure and relatively uniform pores were prepared. Zhou et al [ 13 ] used ZrO 2 as the raw material, MgO and CeO 2 as stabilizers, and prepared ZrO 2 porous ceramics with an excellent performance by sintering organic foam impregnation method. The effects of stabilizer types on shrinkage, surface morphology, and high-temperature phase content of ceramic samples were studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research uses tread designs bio-inspired in a camel hoof and a fennec fox paw and concludes both concepts improved tire traction. Zhou et al 97 used the pads of a cat's paw as inspiration to develop treads that attenuate the vibration of NPTs. Ju et al 26 found that multicellular geometries and TPU materials can reduce the elastic hysteresis loss of NPTs, effectively reducing tire rolling resistance.…”
Section: Mechanical Behaviour Of Nptsmentioning
confidence: 99%
“…For light vehicles, such as light military vehicles and small tractors, it was found that NPT, known as TWEEL, was more suitable with greater stability and mobility than solid tires [ 29 ]. TWEEL can be developed to achieve better characteristics than pneumatic tires using appropriate materials and structures without inflation pressure maintenance [ [30] , [31] , [32] , [33] , [34] ]. Furthermore, the vehicles can be driven even if the NPT is slightly damaged.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, finite element analysis (FEA) was performed to investigate the position, angle, number, and thickness of various spokes that affect the NPT performance [ 40 , 45 , 48 , 49 ]. NPT velocity was an important variable for evaluating riding comfort [ 32 , 49 , 50 ]. FEA was further performed to investigate the NPT interaction with soft ground such as soil and snow [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%